Kemampuan Membaca Pemahaman Teks Anekdot Tulisan Arab Melayu Mahasiswa Kelas 2023 A Pendidikan Bahasa dan Sastra Indonesia Universitas Riau - Rahmi Muliani; Risma Tusa’diah; Sasi Karana; Hasnah Faizah AR (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
This research is motivated by the fact that Riau Malay has Malay Arabic writing, so research activities are needed to determine the ability to read Malay Arabic writing, especially among students. The aim of this research is to provide readers with an understanding of the importance of having the ability to read Malay Arabic for students of the Indonesian Language and Literature Education Study Program and having the ability to read Malay Arabic writing as a form of maintaining existing culture. The type of research carried out is quantitative research, with data collection techniques, namely observation and questionnaires. The results of this research are the ability to read and understand anecdotal texts written in Malay Arabic for class 2023 A students of the Indonesian language and literature education study program at Riau University in the medium category with an average of 79.89.